Chylothorax and Chylopericardium: A Complication of Long-Term Central Venous Catheter Use - James Livesay; Isaac Biney; J. Francis Turner (Case Reports in Pulmonology)
The development of chylothorax and chylopericardium is an uncommon complication of the long-term use of central venous catheters. We describe a unique case of an end stage renal disease patient on hemodialysis with a left jugular tunneled catheter who developed superior vena cava syndrome. Our patient presented with both a large pleural and pericardial effusion that despite drainage continued to reaccumulate. Further imaging with CT scan of the thorax revealed stenosis of the superior vena cava leading to recurrent chylothorax and chylopericardium.